Analyze The Tactical Offensive Principles Of The Algerian National Football Team In The Finals Of The Nations Of Africa 2019 - Boulahia , Mohamed; Mehidi , Mohamed (sports creativity, 2025)
The study aims to identify the strengths and weaknesses of the Algerian national football team with regard to some of the tactical offensive principles of the 2019 African Nations. The researchers used the descriptive approach based on the observation and analysis of the Algerian team's matches in this round. An analysis form comprising 07 offensive tactical principles has been prepared as a data collection tool. The results indicated that the success rate of the support attempts, switch play, switching Positions, creating spaces, and the crossing was good which exceeded to 70%. The success rate of infiltration attempts was moderate (57.86%), while the success rate of the attempts depth mobility was lower than the average (41.51%